Low-grade spindle cell sarcoma of the tonsil: a rare entity - Subha, Sethu Thakachy; Doi, Mohamad; Ahmad Saad, Fathinul Fikri; Mohd Yatim, Nor Yatizah (Iranian Red Crescent Hospital of Dubai, 2023)
Background: Spindle cell sarcoma of the tonsil is an extremely rare malignancy in the head and neck region. The initial clinical presentation can be an asymptomatic mass lesion, and the biopsy of this growing mass should be conducted to exclude a malignant process. In this case report, we described a patient with spindle cell sarcoma of the tonsil with good clinical outcomes after surgery alone. Case presentation: A 38-year-old male presented with a foreign body sensation of the throat, and clinical examination revealed asymmetrical enlargement of the right tonsil. Tonsillectomy was performed, and histopathological examination and immunohistochemistry analysis revealed a low-grade spindle cell sarcoma of the tonsil. He developed local recurrence at 12 months and underwent wide local excision. The patient remained well without any local recurrences and metastases 8 years after diagnosis. Conclusion: We reported this case study in an effort to increase the awareness of spindle cell sarcoma of the tonsil and to emphasize the challenges in the diagnosis of this sarcoma. Surgical extirpation with a clear margin appeared to be an adequate treatment for the low-grade spindle cell sarcoma of the tonsil.